Pengaruh Stimulasi Tumbuh Kembang Ibu yang Menikah Usia Muda Terhadap Pertumbuhan dan Perkembangan Anak Usia di Bawah Lima Tahun (Balita) - Yunarsih Yunarsih; Elfi Quyumi Rahmawati (coba, 2013)
The rapid growth of children in the golden period of growth as indicated by the rapid growth of the brain, indicating the time is very important and can not be repeated. Readiness of the mother in parenting in order to achieve optimal growth and development becomes very important, especially in child care in early life. Nganjuk is one of regencies in East Java that has a young woman's marriage rate is high. The purpose of this study was to determine the relationship between parenting of young aged married mother with the growth and development of children under five years of age. This type of observational study is analytical and uses cross-sectional approach. The population in this study is the mother who married a young age and had children aged under three years old (toddlers) as many as 60 people and obtained the study sample were married for 37 young mothers and have children under three years old. The results showed statistically significant relationship exists between the provision of early stimulation, feeding patterns and hygiene care performed by a mother who married a young age with the growth and development of children under five years of age. On health care and the provision of variable affection showed no association with the growth and development of children under three years of age. It can be caused due to various limitations of the people in the village. Most communities only elementary school education and the level of awareness of the importance of the need for health services is low. Keywords : stimulating, young married mother, child growth and development